Reactions with heterocyclic amidines: Synthesis of several new pyrazolo[1,5-a]pyrimidines and pyrazolo[1,5-a][1,3,5]triazines - Abbas-Temirek, Husien Hasan; Abo-Bakr, Ahmed Mohammed (European Journal of Chemistry, 2016)
N-Bis(methylthio)methylenecyanamide (1) was allowed to react with ethylcyanoacetate or malononitrile in the presence of potassium carbonate in dimethylsulfoxide to yield the urea derivatives (3a,b), which on treatment with hydrazine hydrater resulted the corresponding aminopyrazole derivatives (4a,b). The cyclic amidine 5-amino-3-ureido-1H-pyrazole-4-carboxylic acid ethyl ester (4a) is found to be useful intermediate for the synthesis of new pyrazolopyrimidine and pyrazolotriazine derivatives (5-22a,b). The chemical structures of the synthesized compounds (3a,b-22a,b) were characterized by their elemental analyses, FT-IR, 1H 13C NMR and mass spectra.